Dissecting the cytochrome c2–reaction centre interaction in bacterial photosynthesis using single molecule force spectroscopy. Issue 15 (9th August 2019) - Vasilev, Cvetelin; Mayneord, Guy E.; Brindley, Amanda A.; Johnson, Matthew P.; Hunter, C. Neil
Abstract : The reversible docking of small, diffusible redox proteins onto a membrane protein complex is a common feature of bacterial, mitochondrial and photosynthetic electron transfer (ET) chains. Spectroscopic studies of ensembles of such redox partners have been used to determine ET rates and dissociation constants. Here, we report a single-molecule analysis of the forces that stabilise transient ET complexes. We examined the interaction of two components of bacterial photosynthesis, cytochrome c 2 and the reaction centre (RC) complex, using dynamic force spectroscopy and PeakForce quantitative nanomechanical imaging. RC–LH1–PufX complexes, attached to silicon nitride AFM probes and maintained in a photo-oxidised state, were lowered onto a silicon oxide substrate bearing dispersed, immobilised and reduced cytochrome c 2 molecules. Microscale patterns of cytochrome c 2 and the cyan fluorescent protein were used to validate the specificity of recognition between tip-attached RCs and surface-tethered cytochrome c 2 . Following the transient association of photo-oxidised RC and reduced cytochrome c 2 molecules, retraction of the RC-functionalised probe met with resistance, and forces between 112 and 887 pN were required to disrupt the post-ET RC– c 2 complex, depending on the retraction velocities used. If tip-attached RCs were reduced instead, the probability of interaction with reduced cytochrome c 2 molecules decreased 5-fold. Thus, the redox states of the cytochrome c 2 haem cofactor and RC 'special pair' bacteriochlorophyll dimer are important for establishing a productive ET complex. The millisecond persistence of the post-ET cytochrome c 2 [oxidised]–RC[reduced] 'product' state is compatible with rates of cyclic photosynthetic ET, at physiologically relevant light intensities.